2020
DOI: 10.1155/2020/6634247
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Nine-Redox-Related Long Noncoding RNA Signature in Renal Clear Cell Carcinoma

Abstract: Background. Redox plays an essential role in the pathogeneses and progression of tumors, which could be regulated by long noncoding RNA (lncRNA). We aimed to develop and verify a novel redox-related lncRNA-based prognostic signature for clear cell renal cell carcinoma (ccRCC). Materials and Methods. A total of 530 ccRCC patients from The Cancer Genome Atlas (TCGA) were included in this study. All the samples were randomly split into training and test group at a 1 : 1 ratio. Then, we screened differentially exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 47 publications
1
53
0
Order By: Relevance
“…It gave us insight into their potential role in tumorigenesis and development for KIRC. Also, Xia et al (28) reported the prognostic role of AP006621.2 and AC025580.3 in KIRC. However, the roles of the remaining three m6A-related lncRNAs in tumors have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…It gave us insight into their potential role in tumorigenesis and development for KIRC. Also, Xia et al (28) reported the prognostic role of AP006621.2 and AC025580.3 in KIRC. However, the roles of the remaining three m6A-related lncRNAs in tumors have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…TFPI2 is a matrix related serine protease inhibitor with a Kunitz domain, and plays an important role in angiogenesis, tumorigenesis and metastasis ( 17 , 18 ). As the most important factor in inducing EMT, TGF-β1 can promote the metastasis of various tumor cells ( 19 ). THBS2 is involved in many cellular biological processes by binding EMC protein and cell surface receptor ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports about the clinical relevance of SPINT-AS1 in cancers are inconsistent. SPINT1-AS1 was reported to be associated with good prognosis of renal clear cell carcinoma ( Qi-Dong et al, 2020 ). SPINT1-AS1 was also reported to predict poor prognosis in colorectal cancer ( Li et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%